2022
DOI: 10.3390/cancers14020451
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Extracellular Vesicles in Triple-Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive and refractory subtype of breast cancer, often occurring in younger patients with poor clinical prognosis. Given the current lack of specific targets for effective intervention, the development of better treatment strategies remains an unmet medical need. Over the last decade, the field of extracellular vesicles (EVs) has grown tremendously, offering immense potential for clinical diagnosis/prognosis and therapeutic applications. While TNBC-EVs have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 228 publications
(263 reference statements)
0
13
0
Order By: Relevance
“…The molecular contents of exosomes normally reflect those of their parent cells and can therefore be used as biomarkers for pathophysiological complications (such as cancer). ,, Tumor and stromal cells in the TME have been reported to release exosomes, and their molecular signatures play a dynamic role in cancer. , For example, it has been found that TNBC (triple-negative breast cancer) cells with CCL5 on their surfaces, derived from tumor-derived exosomes, alter TME-associated macrophages and develop a metastatic nature, resulting in a TME favorable for carcinogenesis . Researchers suggest that derived cancer stem cells are involved cancer metastesis .…”
Section: Exosomes For Cancer Theragnosticmentioning
confidence: 99%
See 3 more Smart Citations
“…The molecular contents of exosomes normally reflect those of their parent cells and can therefore be used as biomarkers for pathophysiological complications (such as cancer). ,, Tumor and stromal cells in the TME have been reported to release exosomes, and their molecular signatures play a dynamic role in cancer. , For example, it has been found that TNBC (triple-negative breast cancer) cells with CCL5 on their surfaces, derived from tumor-derived exosomes, alter TME-associated macrophages and develop a metastatic nature, resulting in a TME favorable for carcinogenesis . Researchers suggest that derived cancer stem cells are involved cancer metastesis .…”
Section: Exosomes For Cancer Theragnosticmentioning
confidence: 99%
“…Exosomes are the most interesting noninvasive diagnostic biomarkers and therapeutics. Their cargo molecules are involved in cellular communication. , The secretion of exosomes from specific cells or tissues is based entirely on the cellular and philological condensation of cells . The exosome leads to biologically active molecules .…”
Section: Exosomes For Cancer Theragnosticmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes, on the other hand, are defined by a diameter of 30–100 nm [ 11 , 12 ]. It was their small size that brought exosomes into the focus of drug delivery but also of biomarker research [ 13 ]. They are able to transfer proteins and genetic material [ 14 ].…”
Section: Introductionmentioning
confidence: 99%